Growth prospects, market challenges and policy measures: evolution of mobile broadband in Pakistan. Issue 1 (8th January 2018) - Hanif, Muhammad Shehzad; Yunfei, Shao; Hanif, Muhammad Imran
Abstract : Purpose: The paper aims to explore the long-term prospects of mobile broadband adoption in a developing country. The supply-side and demand-side policy measures are recommended to counter the challenges to broadband adoption. Design/methodology/approach: Methodologically, this study uses document analysis to explain secondary data including growth statistics, trade literature and previous scholarly research. Based on the growth statistics of broadband and the informed market insights, the research discusses the prevailing market threats and recommends counter measures to improve the long-term prospects of broadband propagation. Findings: The growth of mobile broadband is settling down in Pakistan due to various barriers like cost, literacy, security and unavailability of local content. Collaborative efforts are required by the government, the service providers and the people to enhance the adoption of broadband service and secure economic benefits of the broadband. Practical implications: The research offers useful implications for managers and policymakers in Asian and African developing countries; the policy measures discussed here may serve as guidelines for them in the design of their own policies regarding broadband supply and demand. Originality/value: The study makes an effort to examine the broadband growth in a developing country on the basis of both quantitative and qualitative aspects. The research endeavors to fill the gap on the particular scholarship of research covering potential uptake of broadband services and the effects of constraining elements to broadband adoption in a developing country.